2009
DOI: 10.1111/j.1742-4658.2008.06827.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Vibrio mimicus hemolysin through limited proteolysis by an endogenous metalloprotease

Abstract: Vibrio mimicus is a causative agent of human gastroenteritis and food poisoning, and this species produces an enterotoxic hemolysin (V. mimicus hemolysin) as a virulence determinant. Vibrio mimicus hemolysin is secreted as an 80 kDa precursor, which is later converted to the 66 kDa mature toxin through removal of an N‐terminal propeptide via cleavage of the Arg151–Ser152 bond. In this article, we investigate the role of the endogenous metalloprotease (V. mimicus protease) in the maturation of V. mimicus hemoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 36 publications
1
21
0
3
Order By: Relevance
“…Previous studies of a related species, V. vulnificus, have indicated that a metalloprotease, VvpE, may inactivate a hemolysin, VvhA, but there have been conflicting reports (34,35). Studies of V. mimicus and V. tubiashii have also shown a similar relationship between a protease and a hemolysin (14,27). In V. cholerae, HapR increases the expression levels of two genes encoding metalloproteases, hapA and prtV (17,46).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Previous studies of a related species, V. vulnificus, have indicated that a metalloprotease, VvpE, may inactivate a hemolysin, VvhA, but there have been conflicting reports (34,35). Studies of V. mimicus and V. tubiashii have also shown a similar relationship between a protease and a hemolysin (14,27). In V. cholerae, HapR increases the expression levels of two genes encoding metalloproteases, hapA and prtV (17,46).…”
Section: Resultsmentioning
confidence: 79%
“…on May 12, 2018 by guest http://iai.asm.org/ true that deletion of the protease gene resulted in higher rather than lower levels of hemolytic activity, so it was concluded that that metalloprotease is not responsible for proper processing of the hemolysin and in fact leads to degradation of the hemolysin (27). In addition to repressing HlyA activity through HapA, we show that HapR also represses transcription from the hlyA promoter directly.…”
Section: Vol 78 2010 Quorum-sensing Regulation Of Hemolysin 465mentioning
confidence: 85%
“…mimicus produces several extracellular toxic factors, but the most common factor is a heat-labile hemolytic/cytolytic toxin known as V. mimicus hemolysin or VHM (Mizuno et al, 2009;Mizuno, Nanko, Maehara, Shinoda, & Miyoshi, 2014). The VHM gene, vmh, is common to clinical and environmental V. mimicus strains, and it is a species-specific identifier (Shinoda et al, 2004;Sultan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, the proteolytic enzyme that mediates maturation of VMH has not been identified. Recently, a metalloprotease from V. mimicus was found to have the potential to activate pro‐VMH by hydrolysis of the Asn 157 Val 158 bond . However, the main action of the metalloprotease was clarified as inactivation of VMH by digestion of the C‐terminal 15 kDa polypeptide .…”
mentioning
confidence: 99%
“…Recently, a metalloprotease from V. mimicus was found to have the potential to activate pro‐VMH by hydrolysis of the Asn 157 Val 158 bond . However, the main action of the metalloprotease was clarified as inactivation of VMH by digestion of the C‐terminal 15 kDa polypeptide . Interestingly, it was also found that sufficient amounts of mature VMH accumulate in culture supernatants of the metalloprotease‐negative mutant .…”
mentioning
confidence: 99%